2012
DOI: 10.1093/qje/qjs020
|View full text |Cite
|
Sign up to set email alerts
|

The Oregon Health Insurance Experiment: Evidence from the First Year*

Abstract: In 2008, a group of uninsured low-income adults in Oregon was selected by lottery to be given the chance to apply for Medicaid. This lottery provides an opportunity to gauge the effects of expanding access to public health insurance on the health care use, financial strain, and health of low-income adults using a randomized controlled design. In the year after random assignment, the treatment group selected by the lottery was about 25 percentage points more likely to have insurance than the control group that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

75
794
14
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,238 publications
(884 citation statements)
references
References 41 publications
75
794
14
1
Order By: Relevance
“…Natural experiments may include investigations of the effects of policies implemented with a lottery system. For example, Baicker et al recently investigated the effect of the United States' Medicaid insurance program on use of health services, health spending, and clinical outcomes using exogenous variation in program enrollment produced when the Oregon state legislature assigned citizens to program eligibility using a random lottery [46,47]. In most respects, the analysis of data from natural experiments may be identical to the analysis of data from researcher-controlled experiments.…”
Section: Economicsmentioning
confidence: 99%
“…Natural experiments may include investigations of the effects of policies implemented with a lottery system. For example, Baicker et al recently investigated the effect of the United States' Medicaid insurance program on use of health services, health spending, and clinical outcomes using exogenous variation in program enrollment produced when the Oregon state legislature assigned citizens to program eligibility using a random lottery [46,47]. In most respects, the analysis of data from natural experiments may be identical to the analysis of data from researcher-controlled experiments.…”
Section: Economicsmentioning
confidence: 99%
“…Compared with the control group, lottery winners also reported that they were more likely to have a usual doctor, and they had more visits to doctors' offices, prescriptions, and recommended preventive care. 4 Medicaid was associated with improvements in self reported health status and depression, though findings for more objective measures of health (such as cholesterol level) were ambiguous or neutral. 6 However, Medicaid patients experienced around 40% more emergency department visits per person than did the controls.…”
mentioning
confidence: 92%
“…1 This finding was similar to the Oregon experiment, which found no impact on readmissions. 4 Previous studies in Massachusetts have reported increases in utilization of preventive care after reform, 10 more patients having usual places of care, 10 improvements in self reported health status, 11 and increases in emergency department visits. 12 It is hard to generalize from these studies to the effect of the Affordable Care Act, as the context and populations are so different.…”
mentioning
confidence: 97%
See 2 more Smart Citations